2016
DOI: 10.1002/hbm.23324
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing structural neural networks in de novo Parkinson disease patients using diffusion tensor imaging

Abstract: Parkinson disease (PD) can be considered as a brain multisystemic disease arising from dysfunction in several neural networks. The principal aim of this study was to assess whether large-scale structural topological network changes are detectable in PD patients who have not been exposed yet to dopaminergic therapy (de novo patients). Twenty-one drug-naïve PD patients and thirty healthy controls underwent a 3T structural MRI. Next, Diffusion Tensor Imaging (DTI) and graph theoretic analyses to compute individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 81 publications
9
72
0
Order By: Relevance
“…Diffusion tensor imaging (DTI) is a powerful tool to investigate microstructural alterations to the human brain in vivo. In PD, this technique has been combined with voxel‐ or region‐of‐interest (ROI)‐wise (Atkinson‐Clement, Pinto, Eusebio, & Coulon, ; Schwarz et al, ), and graph‐theoretical analyses (Aarabi et al, ; Li et al, ; Nigro et al, ; Pereira et al, ). Tract‐based spatial statistics (TBSS) is a voxel‐wise method, specifically developed to minimize the methodological pitfalls caused by misalignment and misregistration in conventional voxel‐based analyses (Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) is a powerful tool to investigate microstructural alterations to the human brain in vivo. In PD, this technique has been combined with voxel‐ or region‐of‐interest (ROI)‐wise (Atkinson‐Clement, Pinto, Eusebio, & Coulon, ; Schwarz et al, ), and graph‐theoretical analyses (Aarabi et al, ; Li et al, ; Nigro et al, ; Pereira et al, ). Tract‐based spatial statistics (TBSS) is a voxel‐wise method, specifically developed to minimize the methodological pitfalls caused by misalignment and misregistration in conventional voxel‐based analyses (Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…No differences were found between patients and HCs, whereas decreases of efficiency values have previously been shown with fMRI ( 20 22 ) and structural MRI ( 24 26 ). At the whole-brain level, differences in E glob and E loc provide a general indication of disease-associated differences in the integration and segregation capacities of the entire cerebral network.…”
Section: Discussionmentioning
confidence: 52%
“…This is what we have observed in our double DA/5‐HT lesioned monkey model of PD, in which DTI variations were found in many brain structures. In PD patients, DTI alterations take place not only in the SN and the frontal lobe but also in other brain regions (caudate, putamen, pallidum, amygdala, and cingulate cortex) . The presence of disconnectivity mechanisms in motor as well as in nonmotor circuits is coherent with the fact that PD can be considered to be a multisystemic brain disease arising from dysfunction in several networks.…”
Section: Discussionmentioning
confidence: 95%
“…Diffusion tensor imaging (DTI) holds promise for studying abnormalities in both white matter tracts and gray matter areas . Brain diffusion parameters are altered within both the SN (where dopaminergic cell body loss takes place) and projecting structures in early and advanced PD patients. DTI studies in rodent and monkey models of PD have found alterations of diffusion parameters in the SN.…”
mentioning
confidence: 99%